(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article analyzes the theoretical aspects of attracting capital through the stock market by studying the history of its origin and the views of various economists on this issue, as well as work out recommendations for the application of some elements of world experience to increase the flow of capital to the economy through the stock market of Uzbekistan.